Office Kaizen : Transforming Office Operations into a Strategic Competitive Advantage. - Lareau, William (ASQ Quality Press, 2002)
Many business functions have been significantly improved through the use of a variety of quality techniques, but for the most part office and administrative functions have not kept pace. Most companies find it difficult to reduce costs in the office without noticeable sacrifices in performance. Some progressive companies are seeing improvements in their office environments through the use of Office Kaizen, which emphasizes making continuous improvements over the long haul. Office Kaizen: Transforming Office Operations Into a Strategic Competitive Advantage presents a unified, consistent approa.